Standard setting and security returns: A time series analysis of FAS No. 8 events* - CHENG, THOMAS T. (Contemporary Accounting Research, 1986)
This study examines the information content of seven FAS No. 8 related key events on the security returns of firms affected by the accounting rule. The Box and Tiao intervention analysis was used, which combines the univariate ARIMA(p,d,q) (auto‐regressive integrated moving average) modeling with a statistical impact assessment. Results indicate that security returns of firms investigated have generally exhibited patterns of small positive blips (abrupt onsets, temporary durations, and rapid decays) around the time of the appointment of the task force as well as at the date of issuance of the exposure draft. Résumé. Cette étude examine le contenu informationnel de sept événements importants entourant le FAS no 8 sur les rendements des titres d'entreprises affectées par la règle de comptabilité. L'analyse d'intervention Box‐Tiao fut utilisée, méthode où la modélisation ARMNI (p.d.q) à une variable aléatoire est combinée à une évaluation de l'impact statistique. Les résultats indiquent que les rendements des titres émis par les firmes étudiées ont présenté des structures de petites oscillations positives (croissance brutale, durée temporaire et déclin rapide) autour des moments de nomination du groupe d'étude et de publication de l'exposé sondage.